1987
DOI: 10.1016/s0006-3495(87)83231-9
|View full text |Cite
|
Sign up to set email alerts
|

"Resonances" in the dielectric absorption of DNA?

Abstract: An attempt was made to confirm previous reports of resonant-like dielectric absorption of plasmid DNA in aqueous solutions at 1-10 GHz. The dielectric properties of the sample were measured using an automatic network analyzer with two different techniques. One technique used an open-ended coaxial probe immersed in the sample; the other employed a coaxial transmission line. No resonances were observed that could be attributed to the sample; however, resonance-type artifacts were prominent in the probe measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…After some initial reports that frequency specific absorption in plasmids of DNA could occur [Swicord and Davis, 1982;Edwards et al, 1984Edwards et al, , 1985, follow-up investigations revealed that this was not the case [Foster et al, 1987;Gabriel et al, 1987]. This is an important observation, since without evidence of a direct and unique absorption mechanism that could result in redistribution in some manner of the absorbed energy in the molecule, the alternative is that some type of direct bond breakage was occurring.…”
Section: Direct Damage Due To Absorption Of the Rf By Dna In Solutionmentioning
confidence: 98%
“…After some initial reports that frequency specific absorption in plasmids of DNA could occur [Swicord and Davis, 1982;Edwards et al, 1984Edwards et al, , 1985, follow-up investigations revealed that this was not the case [Foster et al, 1987;Gabriel et al, 1987]. This is an important observation, since without evidence of a direct and unique absorption mechanism that could result in redistribution in some manner of the absorbed energy in the molecule, the alternative is that some type of direct bond breakage was occurring.…”
Section: Direct Damage Due To Absorption Of the Rf By Dna In Solutionmentioning
confidence: 98%
“…Furthermore, athermal mechanisms are proposed for rectification by cell membranes (Pickard and Rosenbaum, 1978), which has been observed in plant cells at frequencies below 10 MHz; vibrational resonance in DNA molecules (Edwards, 1984); and structural transformations from random to coiled configurations in polymeric proteins. Careful measurements recently performed in various laboratories have not confirmed the earlier claims of resonance in DNA molecules (Foster, 1987;Gabril, 1987). In addition, the RF hearing phenomena may be considered athermal or microthermal since the temperature rise is very small (as low as 10…”
Section: Introductionmentioning
confidence: 95%
“…In Refs. [16,17], it was demonstrated that there are no microwave resonance effects owing to DNA. An extended analysis in Ref.…”
Section: Introductionmentioning
confidence: 99%